MENGOPTIMALKAN PEMBELAJARAN MATEMATIKA MELALUI KOPERASI SEKOLAH DI SD - Widadari, Wilda; Rita Fiantika, Feny; Prayogo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to optimize mathematics learning in elementary schools (SD) by using school cooperatives as a learning model. The main focus of this research is to improve students' ability to read, write, and count numbers up to 10,000. Mathematics learning through school cooperatives is designed to address the problems found in conventional mathematics learning, such as a lack of student involvement, as well as a limited understanding of basic mathematical concepts. This study uses a qualitative methodology with a phenomenological approach that combines interview, observation, and documentation techniques. The data was analyzed using data analysis techniques. The results of the study show that school cooperatives can be an effective learning model in improving students' basic mathematics skills, with a more interactive and collaborative approach. This study suggests that mathematics learning in elementary schools can integrate more school cooperative practices to create a more holistic learning experience.